Low Level of Development of Professionally Important Characteristics of Future Pilots as a Latent Risk Factor of Flight Safety - Kushnir, Olga (Pedagogical Discourse, 2014)
Based on theoretical and empirical analysis of aviation accidents investigation and the existing system of flight crew professional reliability in civil aviation, it is summarized in this article that there is a need to improve the system of professional training for future pilots in forming and correcting professionally important characteristics. It is also shown data, justifying critical reduction in efficiency measures, taken in previous years (introduction of professional and psychological selection) and information about increasing the problem significance of professionally important characteristics for future pilots at the current stage. In the article it is also discussed a prospective direction of systemic impact on psychological reliability of future pilots by means of teaching methods. The attention is focused on the relevance of permanent psychological and pedagogical impact on the psychological ability of future pilots during their training in higher educational establishment. It is concluded that in the above mentioned problem, it is possible to use research results from advanced occupational psychology.